Effect of Dose of Bokashi Kirinyuh (Chromolaena Odorata) on Growth and Production of Local Corn (Zea Mays L.) - Wa Ode Anti; Samiati Samiati; Sadryanto Munandar; Vivi Anggrasari; La Ode Hidayat (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian, 2021)
The purpose of this study was to determine the effect of the dose of bokashi kirinyuh fertilizer on the growth and production of local maize plants and to determine the amount of bokashi kirinyuh fertilizer, which had the best effect on the development and production of local maize (Zea mays). L.). This research was conducted in Lapolea Village, Barangka District, West Muna Regency, from August to December 2018. This research was arranged based on a one-factor randomized block design (RBD), consisting of four levels of treatment, namely without bokashi kirinyuh fertilizer as a control (K0) fertilizer. bokashi kirinyuh at a dose of 50 g tanaaman-1 (K1), ikirinyuh bokash fertilizer at a dose of 100 g plant-1 (K2) and kirinyuh bokashi at a dose of 150 g plant-1 (K3). The variables observed were plant height (cm), number of leaves (strands), stem diameter (cm), ear length (cm), and production (ton ha-1). The results showed that the application of bokashi kirinyuh fertilizer significantly affected the growth and production of local maize (Zea mays L.). Bokashi fertilizer treatment with a dose of 150 g plant-1 (K3) gave the best effect on the growth and production of local maize plants with an average production of 6.17 tonnes ha-1.